The burden and scope of childhood cancer in displaced patients in Jordan: The King Hussein Cancer Center and Foundation Experience - Rihani, Rawad; Jeha, Sima; Nababteh, Mayse; Rodriguez-Galindo, Carlos; Mansour, Asem; Sultan, Iyad (Frontiers in Oncology, 2023)
Introduction: Jordan hosts one of the highest numbers of refugees per capita in the world, with the Syrian crisis leading to an influx of displaced persons to the already vulnerable population. However, limited resources and a lack of cancer-care strategies have made it difficult for refugees in Jordan to access quality cancer care. The King Hussein Cancer Center (KHCC) and Foundation (KHCF) have played a pivotal role in providing financial and medical support for displaced children with cancer, treating 968 non-Jordanian children with cancer between 2011-2022, with a median age of 6 years. Of these, 84% were fully funded by KHCF, and nationalities included Syrians (29%), Palestinians (26%), Iraqis (23%), and Yemenis (17%). Cancer diagnoses included solid tumors (44%), leukemia (23%), lymphoma (13%), bone sarcomas (9.5%), and retinoblastoma (9.1%). The median cost of treatment was JOD 18,000 (USD 25,352), with a total estimated cost of JOD 23.8 million (USD 33.5 million). More recently, in partnership with St. Jude Children’s Research Hospital (SJCRH), two successive humanitarian funds (HF) were established to optimize cancer care for displaced children in Jordan. Results: Between February 2018 and September 2022, 51 children were fully treated on KHCC-SJCRH-HF, with a median age of 6 years and nationalities including Syrians (80%), Iraqis (6%), and Yemenis (8%). The most common cancer diagnoses were leukemia (41%), lymphoma (25%), solid tumors (24%), retinoblastoma (6%), and brain tumors (4%). Of these, 94% are alive and 51% are still receiving coverage. The median coverage for patients was JOD 21,808 (USD 30,715), and the total cost of treatment on KHCC/KHCF-SJCRH/American Lebanese Syrian-Associated Charities HF1 and HF2 was JOD 1.44 million (USD 1.97 million) and JOD 1.18 million (USD 1.67 million), respectively. Conclusions: This experience highlights the high burden of displaced children with cancer in Jordan, and the importance of local foundations like KHCC/KHCF and partnerships with international partners like SJCRH in providing lifesaving humanitarian initiatives and quality cancer care. Innovative cancer-care delivery models and sustainable financing are essential to ensure continuous coverage and access to cancer care for displaced persons in Jordan.